2020
DOI: 10.2217/cer-2019-0158
|View full text |Cite
|
Sign up to set email alerts
|

Biomedical conferences’ author instructions rarely mention guidelines for reporting abstracts of trials and systematic reviews

Abstract: Aim: To analyze whether instructions for authors of biomedical conference abstracts mention guidelines for writing randomized controlled trial and systematic review abstracts and to evaluate reasons for their absence from instructions. Materials & methods: We analyzed instructions for authors of biomedical conferences advertized in 2019 and assessed whether they mentioned Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Abstracts and Consolidated Standards of Reporting Trial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Still, 2020 instructions for authors of the ASA, ESA, and IARS conference proceedings do not mention any reporting guideline, in contrast to the journals Anesthesiology, European Journal of Anaesthesiology, and Anesthesia & Analgesia [26][27][28][29][30][31]. Only two of 819 instructions for abstracts on conferences had reporting instructions for RCT or systematic review authors [32]. Studies on implementation of CONSORT in journals have shown a potential positive influence on reporting [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…Still, 2020 instructions for authors of the ASA, ESA, and IARS conference proceedings do not mention any reporting guideline, in contrast to the journals Anesthesiology, European Journal of Anaesthesiology, and Anesthesia & Analgesia [26][27][28][29][30][31]. Only two of 819 instructions for abstracts on conferences had reporting instructions for RCT or systematic review authors [32]. Studies on implementation of CONSORT in journals have shown a potential positive influence on reporting [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) for Abstracts, which was originally published in 2013 to foster transparent reporting of systematic review abstracts [10], was updated in 2020 [11]. It has been shown that uptake of these reporting guidelines may not have been optimal [12][13][14], but this will hopefully improve.…”
Section: Discussionmentioning
confidence: 99%